3차원 전기비저항탐사 향상을 위한 수평 전기장 성분 측정법 제안 - 조철현; Churl Hyun Jo; 조인기; In-ki Cho (지구물리와 물리탐사, 2025)
전기비저항탐사는 광물탐사, 토목 및 환경분야 조사 등 천부지구물리탐사 기법중 가장 널리 활용되는 방법으로 주로 공선형배열(collinear array)을 채택하여 수행된다. 이러한 전통적인 현장 자료취득은 전기장의 측선방향성분만을 측정하고 해석하고 있다. 이러한 한계는 2차원 전기비저항탐사(2D ERT)에서는 불가피하지만, 3차원 전기비저항탐사(3D ERT)에서는 중요한 제약으로 작용할 수 있다. 본 연구에서는 전위전극 지점에서 전기장 수평성분을 벡터측정하고 해석하는 방법을 제안한다. 이를 통해 지표전기장 변화의 크기뿐 아니라 방향도 함께 파악할 수 있다. 이와 같은 새로운 측정방식은 3D ERT 역산결과를 향상시킬 것으로 기대한다. Electrical resistivity surveys are one of the most widely used high-resolution near-surface geophysical techniques. However, conventional data acquisition methods based on collinear arrays typically measure and interpret only the electric field components aligned with the survey line. Therefore, the horizontal variations in other directions are neglected. Such a limitation is inherent in two-dimensional electrical resistivity tomography (2D ERT); however, it is a critical constraint in three-dimensional electrical resistivity tomography (3D ERT). Hence, this study proposes a method for the vectorial measurement of the horizontal components of electric field changes at potential electrode stations. This approach enables the determination of both the magnitude and direction of surface electric field variation. The resulting data are expected to improve the resolution and reliability of 3D ERT inversion.